THE RARE PTERIDOPHYTES OF MT. SLAMET WITH THREE SPECIES NEW RECORDS FOR JAVA - Titien Ngatinem Praptosuwiryo (Floribunda, 2013)
It is estimated that Java has about 500 species of Pteridophytes. Nevertheless conservation status of the Pteridophytes in Java has not been provided yet. Therefore inventory on the Pteridophytes of Java and assessing their conservation status are need to be done. The objectives of this study are: (1) to provide the preliminary list of the rare species of Pteridophytes in Mt. Slamet, (2) determine the distribution and habitat of each species. The species was categorized as rare species if it was encountered in less then 10 sites and or the population was less then 20 plants. Random search with belt transect (20 m x 500 m with a sub set 20 m x 100 m) was set up to record the occurence ofspecies in one or more hektar. Twelve species included in 10 genera are recorded as the rare species in Mt. Slamet namely: (1) Asplenium paradoxum Blume, (2) Christensenia aesculifolia (Blume) Maxon, (2) Cyathea glabra (Blume) Copel., (4) Cyathea oinops Hask., (5) Huperzia phlegmaria (L.) Rothm., (6) Pityrogramma austroamericana Domin, (7) Psilotum complanatum Sw., (8) Pteris insignis Mett. Ex Kuhn, (9) Pteris wallichiana J. Agardh., (10) Pyrrosia asterosora (Baker) Hovenkamp, (11) Tectaria zollingeri (Kurz) Holttum, dan (12) Thylacopteris papillosa (Blume) J.Sm. Three species are reported as new records for Java, viz. Pteris insignis, P. wallichiana, and Pyrrosia asterosora. Every species has its own distribution range and habitat characteristics